Análisis de la utilización de algoritmos para la optimización del proceso de adquisiciones en una bodega de productos perecibles, que sirva como base para el desarrollo de una aplicación informática. - Gómez Avilés, Carlos Esteban (2018)
This document presents an analysis on the feasibility of the implementation of algorithms for the optimization of the procurement process in a warehouse of perishable products, which serves as the basis for the development of a computer application, presents relevant information on inventory management and the process of acquisitions in SMEs, development of analysis in databases of academics about related works. Consequently, parameters were established in order to evaluate the most commonly used algorithms in a test environment, select the algorithm with the highest score and implement in a web environment that simulates a real scenario, as well as choosing an optimization model. inventories according to the problem, establishing criteria to evaluate the performance of the application and finally preparing for an architecture proposal for subsequent works that are based on this article for the development of a complete system.